Comparison of chorion allograft and subepithelial connective tissue autograft in the treatment of gingival recession- A randomized controlled clinical trial - Snigdha Maity; Vidya Priyadharshini (Elsevier, 2023)
Background: To compare the clinical outcomes of subepithelial connective tissue graft and chorion membrane along with coronally advanced flap in the treatment of gingival recession. Methods: A total of 12 patients with 24 sites showing isolated bilateral Miller's class I and II gingival recessions were randomly allocated into two treatment sites. One site, connective tissue graft, (n = 12 sites) while on the contra-lateral site, chorion membrane (n = 12 sites) was used with coronally advanced flap. Clinical parameters: probing depth, recession depth, recession width, width of keratinized gingiva, relative attachment level, thickness of keratinized gingiva were recorded at the baseline, 3 months, and 6 months. The amount of root coverage was evaluated after 6 months. Results: Statistically significant differences were observed between test and control sites in terms of recession depth, recession width, width of keratinized gingiva and thickness of keratinized gingiva at 6 months. The test sites presented 66.17 ± 18.85% and the control site showed 87.17 ± 18.33% of root coverage at 6 months. Conclusion: Very limited amount of recession coverage with chorion membrane and did not serve as an alternative to connective tissue graft. Trial registration: CTRI/2017/12/010964.